PENGARUH ASIMETRI INFORMASI DAN MANAJEMEN LABA TERHADAP COST OF EQUITY CAPITAL (Studi Empiris Pada Perusahaan Food and Beverages yang terdaftar di Bursa Efek Indonesia Tahun 2015-2018) - Rika Astutik; Dwi Cahyono; Ibna Kamelia Fiel Afroh (Jurnal Ilmiah Wahana Akuntansi, 2019)
This study aims to examine the effect of information asymmetry and earnings management on the cost of equity capital for food and beverages companies listed on the Indonesia Stock Exchange. Objects in this study are food and beverages companies listed on the Indonesia Stock Exchange and research samples obtained by 11 companies with the study period is the financial year 2015-2018. The independent variables used are information asymmetry and earnings management, while the dependent variable is cost of equity capital. Data analysis method is done by using multiple regression calculation to test the influence of independent variable to dependent variable. The result of the research indicates that information asymmetry is not influence significantly and earnings management is influence significantly to cost of equity capital.